Ironi dalam Novel “Teruslah Bodoh Jangan Pintar” Karya Tere Liye: Analisis Semantik Kognitif - Zikriani, Zikriani; Mulyadi, Mulyadi (Aksara: Jurnal Bahasa dan Sastra, 2025)
This study examines irony in the novel Teruslah Bodoh Jangan Pintar by Tere Liye using a cognitive semantic approach. The research aims to explore the meanings and functions of irony within the novel. Through content analysis, three types of irony were identified: verbal irony, dramatic irony, and situational irony. A total of 10 data points were analyzed, consisting of 3 instances of verbal irony, 6 instances of dramatic irony, and 1 instance of situational irony. Verbal irony appears when the author employs words that contradict their actual meanings, as seen in dialogues that convey subtle yet sharp sarcasm. Situational irony is evident in the disparity between the hopes and realities faced by the characters, such as the failure to attain happiness despite their hard efforts. Dramatic irony occurs when the reader is aware of information unknown to the characters, adding depth to the narrative. The findings of this study reveal that the irony in this novel not only enriches the narrative meaning but also serves as a tool for social critique regarding the depicted situations.Keywords: irony, cognitive semantics, novel, social critique